Peningkatan Literasi Digital Dan Keamanan Informasi Bagi Masyarakat (Studi Pada Kelurahan Padang Serai Kecamatan Kampung Melayu Dalam Transaksi Online Umrah) - Juwita Dwi Syafitri (Yayasan Darussalam Bengkulu, 2024)
The purpose of this study is to improve digital literacy and information security in online Umrah transactions, which often involve fraudulent activities in the name of PT. Hajj and Umrah Travel. The subjects of this study were the residents of Padang Serai Village, Kampung Melayu District, Bengkulu City. The research method used was observation, data collection, and consumer interviews. The results show that consumer interest in performing the Umrah pilgrimage has increased, but financial constraints have forced people to prioritize other interests, such as survival and education costs.